Socioeconomic and environmental impact of PROGAN and PROCAMPO in the municipality of El Oro, Durango - Ríos Rentería, Ismael; Rivera, Patricia (Agricultura, Sociedad y Desarrollo, 2020)
Agriculture and livestock subsidies such as the Direct Support Program to the Farmland (Programa de Apoyos Directos al Campo, PROCAMPO) and the Program for Sustainable Livestock Production and Planning for Livestock and Bee Production (Programa de Producción Pecuaria Sustentable y Ordenamiento Ganadero y Apícola, PROGAN) are generally seen as policies of production increase and commercial alteration; however, they also generate social and environmental impacts. Therefore, this study analyzes their effects both on the socioeconomic development of the producers backed, and on the management of natural resources in the municipality of El Oro, Durango. For this research, we made a literature review, applied a census, and interviewed the key actors of the programs. Results indicate that the objectives of the programs are questionable because even if they contribute partially to the socioeconomic development of producers, inequity prevails in the distribution of economic resources, and in environmental matters it is verified that both programs provoke indirect negative effects, impacting the soil to a greater extent, for example through the increase in the use of herbicides, fertilizers and insecticides, and, to a lesser extent, opening new lands to agriculture.